A novel design biodegradable stent for use in congenital heart disease: Mid‐term results in rabbit descending aorta. Issue 4 (3rd September 2014) - Veeram Reddy, Surendranath R.; Welch, Tré R.; Wang, Jian; Richardson, James A.; Forbess, Joseph M.; Riegel, Matthew; Nugent, Alan W.
<x xml:space="preserve">Abstract</x> Objectives This study evaluates the feasibility of delivery and deployment of low and medium molecular weight (LMW and MMW, respectively) double‐opposing helical (DH) poly‐l‐lactic acid biodegradable stent (BDS) in rabbit descending aorta (DAO). Secondary objectives were to assess patency and inflammation of stented vessels at 9 months and to investigate safety following intentional embolization of stent fragments in DAO. Background A BDS that will relieve aortic obstruction and disappears as the child grows older allowing for preservation of aortic wall elasticity and natural growth of aorta will be ideal to treat Coarctation (CoA). BDS have never been evaluated in the DAO. Methods Seven New Zealand white rabbits underwent implantation of DH‐LMW (n = 7), DH‐MMW (n = 3), and metal stents (n = 7) in DAO. BDS fragments were intentionally embolized into DAO in two rabbits. Results All stents were deployed via a 6‐French sheath. Five BDS covered the origin of major DAO side branches. Angiography and intravascular ultrasound showed good stent apposition to the wall of DAO with minimal luminal loss at 9 months follow‐up. All stents had minimal neointimal hyperplasia on histopathology. Adverse events included 1 death, 1 aortic aneurysm, and lower extremity ulceration due to self‐mutilation in an embolization rabbit. Conclusions Pilot study confirms the feasibility of delivery and deployment of up to 6‐millimeter diameter DH BDS in rabbit DAO. Stent integrity with DH design was maintained at 9 months with minimal vessel inflammation. Potential morbidity due to embolized BD fragments cannot be ruled out and needs further evaluation. © 2014 Wiley Periodicals, Inc.